The Biology of the Nuclear Envelope and Its Implications in Cancer Biology - Alvarado-Kristensson, Maria (Int J Mol Sci, 2019)
The formation of the nuclear envelope and the subsequent compartmentalization of the genome is a defining feature of eukaryotes. Traditionally, the nuclear envelope was purely viewed as a physical barrier to preserve genetic material in eukaryotic cells. However, in the last few decades, it has been revealed to be a critical cellular component in controlling gene expression and has been implicated in several human diseases. In cancer, the relevance of the cell nucleus was first reported in the mid-1800s when an altered nuclear morphology was observed in tumor cells. This review aims to give a current and comprehensive view of the role of the nuclear envelope on cancer first by recapitulating the changes of the nuclear envelope during cell division, second, by reviewing the role of the nuclear envelope in cell cycle regulation, signaling, and the regulation of the genome, and finally, by addressing the nuclear envelope link to cell migration and metastasis and its use in cancer prognosis.